(untitled) (Research, Society and Development, 2021)
Aiming to evaluate the effect of intercropping and organic fertilization on the production of coriander and arugula. The experiment took place at the Experimental Farm of the Federal University of Recôncavo da Bahia (UFRB), in the city of Cruz das Almas-Bahia. The design used was randomized blocks, in split-plots in 3x3 space with five replications. After 33 days of sowing of rocket and 35 of coriander, height, dry and fresh mass of aerial parts of the plants were evaluated. The manure used was cattle and chicken, and the vegetable species were rocket cv. Cultivated and coriander cv. Summer. When the treatments were evaluated individually, the results showed the inefficiency of the intercropping for only the arugula crop. Coriander developed well in the intercropping, showing no difference when compared to the monoculture, but the rocket in the intercropping showed low production when compared to the single crop. As for fertilization, only the single arugula crop showed a difference, with chicken manure being the best for production. For efficient land use (UET) only the intercropping with cattle manure presented an index higher than 1.0; the monoculture of rocket fertilized with chicken manure showed higher gross income and better net income. The operating cost was higher in all treatments involving cattle manure. Considering the economic indices, it is concluded that the intercropping between arugula and coriander is not viable when fertilized with the manure that provided better performance in the intercropping that was the bovine manure.